2015
DOI: 10.1016/j.fbp.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shear stress on the formation and removal of Bacillus cereus biofilms

Abstract: A b s t r a c tThe influence of the shear stress (rw) under which biofilms were formed was assessed on their susceptibility to removal when exposed to chemical and mechanical stresses. A rotating cylinder reactor was used to form biofilms, allowing the simulation of rw conditions similar to those found in industrial settings, particularly in areas with low rw like elbows, corners, valves and dead zones. Bacillus cereus was used as a model bacterium for biofilm formation.Biofilms were formed on AISI316 stainles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 54 publications
4
50
0
2
Order By: Relevance
“…We have shown that PAO1 can respond to shear stresses on the order of millipascals. The shear stresses and rates we apply are 2-100 times smaller than stresses commonly studied for biofilm formation or found in host physiology (34)(35)(36). This suggests that PAO1 and other bacteria may be remarkably sensitive to mechanical stresses in their environment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We have shown that PAO1 can respond to shear stresses on the order of millipascals. The shear stresses and rates we apply are 2-100 times smaller than stresses commonly studied for biofilm formation or found in host physiology (34)(35)(36). This suggests that PAO1 and other bacteria may be remarkably sensitive to mechanical stresses in their environment.…”
Section: Discussionmentioning
confidence: 77%
“…Our work also suggests that the mechanical stresses from the environment, such as shear stress by external flow, to which bacteria are subjected in early biofilm initiation, may impact properties of the mature biofilm. For several bacterial species, biofilms that are grown under high shear are more elastic and denser in matrix proteins and EPS than biofilms grown under low shear (34,35,46). Thus, early enhancement in c-di-GMP time course might allow biofilm-forming bacteria to adapt the strength and resilience of the biofilms formed to better resist mechanical removal.…”
Section: Discussionmentioning
confidence: 99%
“…Turbulence generated during peak flow results in mixing, an increase in oxygenation, bubble generation, and shear stress, which increases detachment rates from sediment and is dependent on bacterial shape and strain, and biofilm cohesive strength (Gomez-Suarez et al, 2001; Young, 2006; Lemos et al, 2014; Figure 1D). The release/resuspension of bacteria from biofilms within sediments is dependent on the combination of physicochemical forcing (Walter et al, 2013) and biotic factors, such as grazing and quorum sensing (Costerton et al, 1995; Kim et al, 2016) which could impact particulate loading to the water column (Figure 1E).…”
Section: Sediments As a Sink/source Of Fecal Bacteria And Viruses?mentioning
confidence: 99%
“…Establishment of B. cereus biofilms on food processing equipment poses a persistent risk to food safety and public health due to the protective effect that the exopolysaccharide matrix confers against cleaners and sanitizers. There is currently increasing interest in biofilm eradication via mechanical clearance, the development of novel antibiofilm material or new antimicrobial agents (Overhage et al 2008;Chaudhari et al 2012;Lemos et al 2015;Pechook et al 2015).…”
Section: Introductionmentioning
confidence: 99%